2007
DOI: 10.1111/j.1365-2621.2007.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of sour‐cherry juice and concentrate

Abstract: Rheological properties of sour cherry juice were determined by a Controlled Stress Rheometer. Sour cherry juice with different solid contents (40, 45, 50, 55, 60, 65, 68.5 and 70 Brix) was prepared using a rotary evaporator after squeezing and filtration of sour cherries. The rheological behavior of these concentrates was studied in the temperature range of 5, 10, 20, 30, 40, and 50°C. Sour cherry juice was found to exhibit Newtonian behavior. The effect of temperature on viscosity can be described by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 7 publications
3
32
0
1
Order By: Relevance
“…According to Telis-Romero et al [32], high values of activation energy mean that there is a large effect of temperature on the considered property. Akbulut et al [20], who used a similar to Equation (14) model for the viscosity of Juniperus drupacea fruit juice with a total soluble solids concentration varying from 62.8 to 75.2%, reported an activation energy value of 70.37 kJ/mol, whereas [14,17]. In addition, once the structure responsible for thixotropy was destroyed, there was also a lower effect of solids concentration on the viscosity than that in forward and backward measurements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Telis-Romero et al [32], high values of activation energy mean that there is a large effect of temperature on the considered property. Akbulut et al [20], who used a similar to Equation (14) model for the viscosity of Juniperus drupacea fruit juice with a total soluble solids concentration varying from 62.8 to 75.2%, reported an activation energy value of 70.37 kJ/mol, whereas [14,17]. In addition, once the structure responsible for thixotropy was destroyed, there was also a lower effect of solids concentration on the viscosity than that in forward and backward measurements.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Belibagli and Dalgic [17], Altan and Maskan [14], Nindo et al [15], Khalil, Ramakrishna, Nanjundaswamy and Patwardhan [34], and Rao, Cooley, and Vitali [35] reported that clarified sour-cherry, pomegranate, blueberry, raspberry, and banana juices and depectinized clarified apple juice exhibit Newtonian behavior at all concentrations and temperatures. According to Zuritz et al [16], the clarified juice concentrates have a Newtonian behavior, although Ibarz et al [21] have found a small pseudoplasticity in the flow of various fruit concentrates due to the presence of some soluble solids, mostly pectins and tartrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary experiments showed no significant dependence or slight thixotropy for mume pulp (BELIBAGLI and DALGIC, 2007). Table 1 showed that the yield stress (τ 0 ) did not show consistent behaviour with regards to the variation in temperature between 15 and 75 °C for mume pulp from 6 to 9 °Brix.…”
Section: Discussionmentioning
confidence: 99%
“…The Arrhenius equation is commonly used for rheological studies reported in the literature, and the effect of temperature on the viscosity can be determined in juices and pulps (ARSLAN et al, 2005;BELIBAGLI and DALGIC, 2007;FALGUERA and IBARZ, 2010;VANDRESEN et al, 2009):…”
Section: Discussionmentioning
confidence: 99%